The Use of Middle Voice in Narrativizing Trauma in Bimal’s “The Lankuri Will Blossom Again” - Pokharel, Badri Prasad (KMC Research Journal, 2023)
This article analyzes Rajendra Bimal’s “The Lankuri Tree Will Blossom Again”, a story written on the background of the ten-year-long Maoist insurgency in relation to trauma theory, especially Dominick LaCapra’s concept of middle voice which elucidates the neutrality in narrativization of any traumatic past. The article tries to find out how the narrator while presenting his or her traumatic testimony about a horrible event narrates it - objectively elucidating all the incidents neutrally as a neutral observer of the event not aligning with any fighting groups which would subsequently help both groups to accept the testimony as their own and realize their past agony and purgate their foes. If the testimony of historical events is narrated idealizing one and demonizing another group, it, later on, cannot be accepted as an authentic one and the condition of the victims of the events would be more aggravated as it cannot appease their tension. The testimony of the ten-year-long insurgency by any neutral observer can help many people narrativize their experience in the written form.